Rasch Modeling of the Test of Early Mathematics Ability–Third Edition With a Sample of K1 Children in Singapore. (September 2017) - Yao, Shih-Ying; Muñez, David; Bull, Rebecca; Lee, Kerry; Khng, Kiat Hui; Poon, Kenneth
The Test of Early Mathematics Ability–Third Edition (TEMA-3) is a commonly used measure of early mathematics knowledge for children aged 3 years to 8 years 11 months. In spite of its wide use, research on the psychometric properties of TEMA-3 remains limited. This study applied the Rasch model to investigate the psychometric properties of TEMA-3 from three aspects: technical qualities, internal structure, and convergent evidence. Data were collected from 971 K1 children in Singapore. Item fit statistics suggested a reasonable model-data fit. The TEMA-3 items were found to demonstrate generally good technical qualities, interpretable internal structure, and reasonable convergent evidence. Implications for test development, test use, and future research are further discussed.